The seismic SPT to determine the maximum shear modulus - Pedrini, R. A A [UNESP]; Giacheti, H. L. [UNESP] (My University, 2013)
This paper presents the first results of a system to carry out seismic SPT, which associates the up-hole seismic technique to the currently used SPT test. This hybrid test allows determining the maximum shear modulus (G 0) together with the SPT test. G 0 is the most important dynamic soil parameter and it is calculated based on the shear wave velocity (V S) measurements. The equipment and the method of analysis will be briefly described. The V s values measured using the S-SPT in one experimental research site located inland of Sao Paulo State-Brazil are presented and compared with down-hole and Seismic CPT test data. These preliminary results indicate that the S-SPT was satisfactory and can be used for dynamic site characterization.
Keywords: G 0; SPT test; Up-hole; V s; Experimental research; Hybrid tests; Maximum shear modulus; Method of analysis; Sao Paulo; Seismic technique; Shear wave velocity; Site characterization; Soil parameters; Test data